Parenting a Child with Asperger's Syndrome - Irawati, Sutiyah Nova (JOURNAL OF EARLY CHILDHOOD EDUCATION STUDIES, 2021)
This study provides an interpretive description of parents’ experiences of raising a child with Asperger’s syndrome (AS). Thirteen parents (eight mothers; five fathers) from eight families participated. Data were com-prised of repeated semi-structured interviews with parents. The core concept of a ‘‘balancing act’’ was identified, and included two key themes: losing our footing and regaining our balance. Parents lost their footing when they experi-enced escalating challenges and lack of parenting success. They persevered over many years to find an answer to their children’s problems. The diagnosis of AS was a turning point that initiated the process of ‘‘regaining our balance,’’ enabling parents to better understand both their children and the condition. In this part of the process parents gradually experienced parenting success and rebuilt their confidence. The results of this study suggest that parenting a child with AS is a complex and evolving process in which parents struggle to find the right balance for themselves, their child with AS, and their family as a whole. Parenting encompassed joys and sorrows and an important part of finding balance included the ability to acknowledge both the positive qualities of their children and the challenges of managing the condition. Lack of professional recognition of AS, as well as blame and stigma, negatively affected these participants’ ability to parent and points to the critical need for further education of teaching and health professionals.